Stakeholder analysis for hypertension management in the context of the Indian public health system - Nilanjana Ghosh; Venkatesh Karthikeyan; Shubhabrata Das; Pallavi Boro; Sasthi Narayan Chakraborty (Wolters Kluwer Medknow Publications, 2023)
Background: Hypertension (HTN) portends a significant public health burden in India and calls for multi-stakeholder action. Objectives: We aimed to analyze the role of key stakeholder constituencies implicated in managing HTN across different levels of care within the public health system in India, alongside the enablers and barriers for effective program implementation. Methods: We reviewed 45 articles and policy documents, and 17 consenting stakeholder representatives scored the stakeholder constituencies for "power," "position" and "interest." They ranked enablers and barriers to noncommunicable disease programs in each of the six building blocks of the WHO Health System Strengthening Framework. Data were analyzed on Jamovi 2.2.2. Results: Policymakers/program managers emerged as the most critical stakeholder in influencing policy implementation (score for power: 23.3 ± 8.5, position: 25.4 ± 6.9, and interest: 22.1 ± 8.3). Beneficiaries ranked lowest (power: 10 ± 5.1, position: 12.3 ± 4.5, and interest: 19.4 ± 4.2). Effective "on-ground" implementation ("service delivery") was the most important enabler (17.9 ± 3.3) as well as a barrier (17.6 ± 9.2). The health workforce (19.2 ± 4.8) emerged as a top barrier. Conclusion: To bring around impactful efficiency in the health system, provider-side interventions, especially those at the point of delivery, emerged as the need of the hour. Policymakers and program managers could lead using a top-down leadership and Governance Approach, focusing on deploying an adequately trained and motivated health workforce to deliver HTN services. For ensuring better performance of the health system for HTN care, the health workforce/seemed to be the "obligatory pivot." Health-care providers could serve as the "point of convergence" of efforts made by all the stakeholder constituencies.